Penanaman Nilai-Nilai Toleransi Beragama Siswa Melalui Budaya Sekolah di SMP Negeri 13 Seluma - Yelmi Novita Piqrian; Hery Noer Aly (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2024)
This research aims to: (1) find out how to instill the value of religious tolerance in students through school culture at SMP Negeri 13 Seluma. (2) to find out what are the supporting and inhibiting factors in cultivating the values of religious tolerance in students through school culture at SMP Negeri 13 Seluma. This research uses a qualitative approach and descriptive research type. Data collection methods include observation, interviews and documentation. The collected data is then selected and analyzed through; Data reduction; Presentation of data and then conclusions drawn. The focus of this research is on instilling the value of religious tolerance through school culture and the obstacles and solutions in instilling the value of religious tolerance through culture at SMP Negeri 13 Seluma. This research aims to find out how to instill the value of religious tolerance through school culture and the obstacles and solutions in instilling the value of religious tolerance through the culture of SMP Negeri 13 Seluma. Based on the research results, instilling the value of religious tolerance in students through the culture of SMP Negeri 13 Seluma consists of 3 stages, namely: first, it is integrated into school policy, second, teachers set a good example, third, students are used to having the value of religious tolerance. The obstacle in instilling the value of religious tolerance through school culture lies in students who have attitudes that are too fanatical, because they come from families that are too fanatical. The solution in this case is that there must be good relationships and communication between teachers and parents in instilling the value of religious tolerance.